Radiosensitization of Cancer Cells by Inactivation of Cullin-RING E3 Ubiquitin Ligases - Wei, Dongping (Neoplasia Press Inc., 2012)
Although radiotherapy represents one of the most effective treatment modalities for patients with cancer, inherent and/or acquired resistance of cancer cells to radiotherapy is often an impediment to effective treatment. Diverse strategies have been developed to improve the efficacy of radiotherapy. The ubiquitin-proteasome system (UPS) operates in numerous vital biologic processes by controlling the protein turnover in cells. Ubiquitination is central to the UPS pathway, and it relies on the E3 ubiquitin ligases to catalyze the covalent attachment of ubiquitin to its protein substrates. Cullin-based RING ligases (CRLs) are the largest family of E3 ligases that are responsible for the ubiquitination and destruction of numerous cancer-relevant proteins. Its deregulation has been linked to many human cancers, making it an attractive target for therapeutic intervention. This review discusses how targeting the ubiquitin-proteasome system, particularly CRLs, is an exciting new strategy for radiosensitization in cancer and, specifically, focuses on MLN4924, a recently discovered small-molecule inhibitor of the NEDD8-activating enzyme, which is being characterized as a novel radiosensitizing agent against cancer cells by inactivating CRL E3 ubiquitin ligases.